Characterization Of Physico-Chemical And Film Properties Of Hemicelluloses B From Oil Palm Frond (Elaeis Guineensis) - Halim, Noor Haliza Abdul (2010)
Hemicelluloses B (HB) from oil palm frond (OPF) were extracted using three alkaline concentration (1.0, 2.0 and 3.0M KOH) at 40 oC for 4 hours, respectively. HB extracted was then characterized based on monosaccharide composition, uronic acid, molecular structure, molecular weight, crystallinity and thermal stability in order to study the effect of different alkaline extraction on HB from OPF. HB extracted from all alkaline concentrations were casted and their film properties were investigated. The increase in KOH concentration from 1.0 to 2.0 and 3.0 M, were observed to increase the yields of each fraction from 5.0 to 8.7 and 9.5 %, respectively.